Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2018
DOI: 10.1111/mice.12417
|View full text |Cite
|
Sign up to set email alerts
|

Short‐Term Traffic Speed Forecasting Based on Attention Convolutional Neural Network for Arterials

Abstract: As an important part of the intelligent transportation system (ITS), short-term traffic prediction has become a hot research topic in the field of traffic engineering. In recent years, with the emergence of rich traffic data and the development of deep learning technologies, neural networks have been widely used in short-term traffic forecasting. Among them, the Recurrent Neural Networks (RNN), especially the Long Short-Term Memory network (LSTM) shows the excellent ability of time-series tasks. To improve the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
62
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 138 publications
(78 citation statements)
references
References 41 publications
0
62
0
Order By: Relevance
“…Attention mechanism has been widely utilized in traffic prediction tasks to improve the performance of the models, [37], [38]. With attention block, one model can focus on important features and suppressing unnecessary ones [39].…”
Section: Convolutional Block Attention Modulementioning
confidence: 99%
“…Attention mechanism has been widely utilized in traffic prediction tasks to improve the performance of the models, [37], [38]. With attention block, one model can focus on important features and suppressing unnecessary ones [39].…”
Section: Convolutional Block Attention Modulementioning
confidence: 99%
“…The results showed that the proposed method outperformed LSTM model by a mean squared errors improvement of 42.91%. Using the traffic speed data from the Caltrans Performance Measurement System (PeMS), Liu et al [43] predicted traffic speed by the attention convolutional neural network (ACNN) model and found that the proposed model achieved better forecast results than traditional linear models.…”
Section: Short-term Traffic Speed Predictionmentioning
confidence: 99%
“…The attention allows for more direct dependence between the states of the model at different time steps by integrating with other deep models, eg, CNNs or RNNs. Liu et al proposed an attention‐based CNN model for traffic speed prediction, which employed CNN to extract spatial and temporal features of traffic data, and simultaneously utilized attention to weight feature maps and channels to enhance the validity of the learned features. Moreover, the attention‐based RNNs have been successfully applied to sequence learning and traffic prediction .…”
Section: Related Workmentioning
confidence: 99%